Management of finance of the organizations in the conditions of new economic realities - A. V. Rusavskaya (Путеводитель предпринимателя)
In new economic realities the effective model of organizations finance management considering the interests of the state, financial and credit sphere, shareholders and workers is necessary. Modern financial management has to promote improving competitiveness of the organizations, their financial stability and investment attractiveness.